2013
DOI: 10.15343/0104-7809.2013374458463
|View full text |Cite
|
Sign up to set email alerts
|

O significado de qualidade de vida para cuidadores de enfermagem em uma unidade de terapia intensiva adulto

Abstract: ResumoA qualidade de vida dos cuidadores de enfermagem que atuam em UTI tem sido foco de inúmeros estudos nas últimas décadas. Este estudo teve como objetivo identificar o significado de qualidade de vida atribuído pelos cuidadores de enfermagem que atuam em uma UTI para adultos. Trata-se de um estudo descritivo-exploratório, com abordagem qualitativa. Observaram-se cinco núcleos temáticos que deram sentido ao significado de qualidade de vida: QV como bem--estar biopsicosocioespiritual; tempo para a vida famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 11 publications
0
5
0
11
Order By: Relevance
“…Much of these professionals' lives is spent in these hospital settings, mainly due to the long working hours. Studies, especially in the nursing area, have shown that QOL is associated with the conditions offered in these locations (4,(6)(7)(8)(9)(12)(13) and, when coupled with a sedentary lifestyle, it can influence the health-disease process. A sedentary lifestyle, along with smoking and bad eating habits are risk factors for the development or worsening of NCDs (14)(15)(16)(17)(18)(19)(20)(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of these professionals' lives is spent in these hospital settings, mainly due to the long working hours. Studies, especially in the nursing area, have shown that QOL is associated with the conditions offered in these locations (4,(6)(7)(8)(9)(12)(13) and, when coupled with a sedentary lifestyle, it can influence the health-disease process. A sedentary lifestyle, along with smoking and bad eating habits are risk factors for the development or worsening of NCDs (14)(15)(16)(17)(18)(19)(20)(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…As physicians in the area have a contract of up to 12 hours, they can work in more than a job, or even increase their shift hours in the same job and thereby, increase their working hours. Another important issue was that about 61% of participants had more than a job, which is considered one of the physical and psychological stress factors for workers in the health area (9,12) . The results of this study have shown that volunteers considered as active had better scores on the SF-36 domains when compared to the inactive, as well as lower working hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A baixa remuneração e a necessidade de complementar a renda podem levar alguns profissionais a buscarem mais de um emprego e isto vir a comprometer sua qualidade de vida 1,2 . Esta situação pode exceder a carga horária máxima recomendada para o trabalhador no Brasil, que segundo a Consolidação das Leis do Trabalho (CLT) 3 é de 44 horas semanais, diminuindo o tempo livre para práticas de atividade física, lazer, cuidados com a saúde e consequentemente afetando a qualidade de vida (QV).…”
Section: Introductionunclassified
“…Pessoas fisicamente ativas apresentam maior vigor e vontade de realizar suas atividades diárias e profissionais, além de demonstrarem maior energia e menor cansaço, colaborando para a melhora das relações interpessoais, tais como familiar e socialização no trabalho 12 Vários estudos [13][14][15] têm apresentado atenção especial para a jornada de trabalho em diferentes profissionais, entretanto, pouco se tem estudado sobre a sua relação com nível de atividade física e QV dos profissionais que trabalham em unidade de terapia intensiva, setor hospitalar com características próprias, como o ambiente fechado, contato com o sofrimento, dor e morte, atenção sempre constante e situações inesperadas que exigem alta interdependência [16][17][18][19] . Profissionais que trabalham nesse setor, muitas vezes estão trabalhando acima da carga horária recomendada, podendo comprometer a sua QV e influenciar negativamente o seu funcionamento, afetando a capacidade do serviço prestado 1,2 .…”
Section: Introductionunclassified